Full-time schooling, part-time schooling, and wages: returns and risks in Portugal - Corrado Andini; Pedro Telhado Pereira (Institute for the Study of Labor (IZA), 2007)
The standard wage equation proposed by Mincer (1974) assumes that individuals start working after leaving school, which is not the actual case for many people. Using longitudinal data on Portuguese male workers, former working students, we estimate the total impact of an additional year of full-time schooling on both the mean and the shape of the conditional wage distribution. The same exercise is also performed for part-time schooling. We find that the conditional average earnings return to one year of part-time schooling is much lower than the analogous return to one year of full-time schooling. However, the conditional wage risk implied by one year of part-time schooling is much lower than the analogous risk implied by one year of full-time schooling, thus complicating policy considerations. Nevertheless, we find evidence that the full-time schooling strategy dominates, in conditional wage distribution, the part-time schooling strategy, meaning that the choice of working while enrolled in school does not ultimately pay
urn:nbn:de:101:1-20080416106
Keywords: 330; Lohn; Bildungsertrag; Bildungsverhalten; Berufsbegleitende Ausbildung; Portugal